Factors influencing poor academic performance among urban university students in Bangladesh - M. Shahjahan; Kazi Rumana Ahmed; Ahmed Al Hadrami; Md. Rabiul Islam; Sharmin Hossain; Md. Sabur Khan (International Journal of Evaluation and Research in Education (IJERE), 2021)
Poor academic performance is challenging for students, parents, and teachers. This cross-sectional study aimed to determine the factors associated with the poor academic performance of 661 undergraduate students who scored CGPA ≤2.5 from a selected private university of Dhaka City, Bangladesh, using a simple random sampling technique. Data were collected using a pretested and self-administered questionnaire. Of the study participants, male preponderance (88.4%) was found, and 77.9% of them selected the study programs by themselves. Poor academic performance was found significantly correlated with irregular class attendance (p=0.003), father’s low education level (p